Sometimes we tell the truth - Zarins, Kim (Pulse, 2016)
A contemporary retelling of "The Canterbury Tales" follows the experiences of a group of teens on a bus trip to Washington, DC, who exchange fantastical, realistic, and scandalous stories in the hopes of achieving a top grade in their class.